Domestication of crazy fish (Butis butis) by being given different natural feed - Ika Nazira Lubis; Khairul Khairul; Helentina Mariance Manullang (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to find out absolute length growth, absolute weight, and survival rate of crazy fish (Butis butis) domesticated by being given different natural feed. This research is experimental. The maintenance container used is in the from of two plastic drums with a capacity of 70 liters. Fish are kept in each container as many as 10 individuals for 1 month. Treatment A, fish fed jawla paste shrimp (Acetes sp) and Treatment B, fish fed mosquito larvae (Culex sp). After 1 month the fish is kept then taken data on the absolute length growth, absolute weight, as well as the survival rate of its life. The absolute length and absolute weight of the fish ware analyzed with Paired T Test with Statical Product and Survive Solutions (SPSS) version 22 to determine the differences between treatment. The results of data analysis related to the growth of absolute length ang absolute weight of crazy fish effect in non significant. Average absolute length growth in Treatment A (0.3) and Treatment B (0.325 cm). Average absolute weight growth in Treatment A (1.044 g) and Treatment B (0.721 g). Survival rate of fish fed jawla paste shrimp by 90% and those fed mosquito larvaes by 80%.